Improvement in perioperative care in pediatric cardiac surgery by shifting the primary focus of treatment from cardiac output to perfusion pressure: Are beta stimulants still needed?. (5th June 2017) - Hosseinpour, Amir‐Reza; van Steenberghe, Mathieu; Bernath, Marc‐André; Di Bernardo, Stefano; Pérez, Marie‐Hélène; Longchamp, David; Dolci, Mirko; Boegli, Yann; Sekarski, Nicole; Orrit, Javier; Hurni, Michel; Prêtre, René; et al.
Abstract: Objective: An important aspect of perioperative care in pediatric cardiac surgery is maintenance of optimal hemodynamic status using vasoactive/inotropic agents. Conventionally, this has focused on maintenance of cardiac output rather than perfusion pressure. However, this approach has been abandoned in our center in favor of one focusing primarily on perfusion pressure, which is presented here and compared to the conventional approach. Design: A retrospective study. Setting: Regional center for congenital heart disease. University Hospital of Lausanne, Switzerland. Patients: All patients with Aristotle risk score ≥8 that underwent surgery from 1996 to 2012 were included. Patients operated between 1996 and 2005 (Group 1: 206 patients) were treated according to the conventional approach. Patients operated between 2006 and 2012 (Group 2: 217 patients) were treated according to our new approach. Interventions: All patients had undergone surgery for correction or palliation of congenital cardiac defects. Outcome measurements: Mortality, duration of ventilation and inotropic treatment, use of ECMO, and complications of poor peripheral perfusion (need for hemofiltration, laparotomy for enterocolitis, amputation). Results: The two groups were similar in age and complexity. Mortality was lower in group 2 (7.3% in group 1 vs 1.4% in group 2, P < .005). Ventilation times (hours) and number of days on inotropic/vasoactive treatment (all agents), expressed as median and interquartile range [Q1–Q3] were shorter in group 2: 69 [24–163] hours in group 1 vs 35 [22–120] hours in group 2 ( P < .01) for ventilation, and 9 [3–5] days in group 1 vs 7 [2–5] days in group 2 ( P < .05) for inotropic/vasoactive agents. There were no differences in ECMO usage or complications of peripheral perfusion. Conclusions: Results in pediatric cardiac surgery may be improved by shifting the primary focus of perioperative care from cardiac output to perfusion pressure.